Preparation and Characterization of Silver Nanospheroids: Theoretical and Experimental Approaches - Amraoui, Mounira; Daoudi, Chouaib; Remram, Mohamed (Photonics Letters of Poland, 2017)
We synthesized silver nanoparticles of different sizes and forms as function of the molar masses of AgNO3, in two different solvent mediums (ethanol, methanol). We carried out the synthesis according to standard chemical route with major modifications. The spectroscopic characterization showed the presence of two distinct absorption bands; the first band at 300 nm and the second shifted to 440 nm. We found a multipolar phenomenon depending on the temperature. The shape and size predicted by the numerical model are conform to the experimental results. The study demonstrated that the nanoparticles have a spheroidal shape. Full Text: PDF References Cecilia Noguez, "Surface Plasmons on Metal Nanoparticles: The Influence of Shape and Physical Environment", J. Phys. Chem. C 111(10), 3806 (2007). CrossRef M. Amraoui , C. Daoudi and M. Remram, Int.Sc.Sci and Tech. Conf. 2015 Ayd?n,Turkey , 11-13 May , 2015 (ISSTC 2015). M. I Gonzalez-Sanchez et al, "Silver nanoparticle based antibacterial methacrylate hydrogels potential for bone graft applications", Mater. Sci. Eng C. Mater. Biol. Appl 50, 332 (2015). CrossRef Xinyi Dong et al, "Shape Control of Silver Nanoparticles by Stepwise Citrate Reduction", J. Phys. Chem. C 113(16), 6573 (2009). CrossRef A. Wolak, M. Grabiec, O. Véron, J. ?P. Blondeau and K. Dzierżęga, "Nanosecond infrared laser-induced precipitation of silver nanoparticles in glass", Phot. Lett. Poland 5(2), 54 (2013). CrossRef A. Zielinska, E. Skwarek, A. Zaleska, M. Gazda and J. Hupka, "Preparation of silver nanoparticles with controlled particle size", Procedia Chemistry 1, 1560 (2009). CrossRef K-S.Chou, Y.Chang and L. Hua, "Studies on the Continuous Precipitation of Silver Nanoparticles", Ind.Eng.Chem.Res 51(13) 4905 (2012). CrossRef A. M. Atta, H. A. Al-Lohedan, A. O. Ezzat, "Synthesis of Silver Nanoparticles by Green Method Stabilized to Synthetic Human Stomach Fluid", Molecules 19(5) 6737 (2014). CrossRef Botasini, S, Méndez, E. "Silver nanoparticle aggregation not triggered by an ionic strength mechanism", J Nanopart Res 15, 1526 (2013). CrossRef V. Amendola, O.M. Bakr, F. Stellacci, "A Study of the Surface Plasmon Resonance of Silver Nanoparticles by the Discrete Dipole Approximation Method: Effect of Shape, Size, Structure, and Assembly", Plasmonics 5(1) 85 (2010). CrossRef L. Jeong, W. Ho Park "Preparation and Characterization of Gelatin Nanofibers Containing Silver Nanoparticles", Int. J. Mol. Sci 15, 6857 (2014). CrossRef Peter Monk, Finite element method for Maxwell's equations, (Oxford, Clarendon Press 2003). DirectLink M.D. Abramoff, P.J. Magalhaes, S.J. Ram, "Image processing with ImageJ", Biophotonics International 11(7), 36 (2004). DirectLink Edward D.Palik, Handbook of optical constants of solids (California, Academic Press Inc, 1985). DirectLink